Influence of Quality, Service, Atmosphere on Satisfaction via Buying Interest – Season Coffee - Gerry Agave Prasetia; Meitiana Meitiana; Vivy Kristinae; Noorjaya Nahan (Penerbit Goodwood, 2025)
Purpose: This study aimed to examine the influence of product quality, service quality, and store atmosphere on customer satisfaction, with purchase intention as a mediating variable at Season Coffee in Kasongan. This study is motivated by the increasing competition in the coffee shop industry, where customer satisfaction is shaped by the quality of products, service delivery, and store ambiance. Methodology/Approach: A quantitative approach with an associative method was used. Data were collected using questionnaires distributed to 100 active customers of Season Coffee. Structural Equation Modeling (SEM) using Partial Least Squares (PLS) with SmartPLS 3.0 was used for data analysis. Results/Findings: The findings indicate that product quality, service quality, and store atmosphere each have a positive and significant effect on purchase intention. Moreover, purchase intention significantly influenced customer satisfaction and mediated the relationship between the three independent variables and customer satisfaction. Conclusions: The results suggest that enhancing product quality, improving service performance, and optimizing store ambiance can effectively increase customers’ purchase intentions, which, in turn, improves overall customer satisfaction. Therefore, coffee shop businesses should focus on these key elements to strengthen customer loyalty and competitive advantage. Limitations: This study is limited to a specific demographic in Kasongan and may not fully represent the broader customer base of the Seasons Coffee. Contribution: This study contributes to the development of consumer behavior models in Indonesia’s coffee shop industry and provides empirical support for the mediating role of purchase intention between service attributes and customer satisfaction.